O efeito da melatonina na angiogênese e metástase de linhagens de carcinoma epidermóide bucal - Rodrigues, Rodrigo Ventura [UNESP] (2013)
Oral cancer is the most common type of cancer of the head and neck and its high mortality and morbidity is closely related to the processes of angiogenesis and metastasis. Overexpression of Hypoxia-inducible factor 1-alpha - HIF1 – -, Vascular Endothelial Growth Factor – VEGF - and Rho-associated serine-threonine protein kinase - ROCK1 - are related to poor prognosis in oral carcinoma. Melatonin has oncostatics, antiangiogenic and antimetastatics properties in several types of cancer, however, its action in oral cancer is underexplored This study aimed to analyze the expression of genes in the process of angiogenesis and metastasis in squamous cell carcinoma cell lines of tongue after treatment with melatonin. The lines SCC4, SCC9, SCC15 and SCC25 were tested, and the lines SCC9 and SCC25 were selected for this study. The action of melatonin was observed under conditions of normoxia and hypoxia by quantitative qRT-PCR and immunocytochemistry in gene and protein expression of HIF1 - , VEGF and ROCK1. The results showed that there was a decrease in cell viability in SCC25 strains after the treatment with melatonin. The analysis showed the inhibition of gene expression of proangiogenics genes HIF1 - (P < 0.001) and VEGF (p <0.001) under hypoxic conditions and prometastatic gene ROCK1 (P < 0.0001) in the line SCC9 , after treatment with 1 mM melatonin. The immunocytochemistry analysis confirmed the gene expression data, validating the results of quantitative qRTPCR of lineage SCC9. Treatment with melatonin did not show inhibition of the expression of HIF- 1 , VEGF and ROCK1 in the line SCC25, which has different molecular characteristics and degree of malignancy greater when compared to the line SCC9. In conclusion melatonin affects cell viability in the strains SCC9 and SCC25 and inhibits gene expression of HIF1 - , VEGF and ROCK1 in the line SCC9. The potential therapeutic effect of melatonin in these subtypes of oral cancer can be ...